Factors of Reading Skills in English for Adults - Rahayu, Rian Sri (Adpebi Science Series, 2022)
This paper aims to reveal factors that influence reading skills for adults. Qualitative research was done towards two categories of freshmen major in Management in Universitas Pamulang. Observations and interviews were used to collect data from two categories of freshmen. Oral reading accuracy was used as a component of reading skill assessment in observations. The results showed that the use of the language and the fondness to the language itself influence reading skills for adults.